Mendelian Randomization Analysis Supports a Causal Relationship Between Circulating Inflammatory Proteins and Basal Cell Carcinoma - Fu ZD; Wang Y; Yan HL; Wu JH (Clinical, Cosmetic and Investigational Dermatology)
Zhi-da Fu,1,2,* Yao Wang,3,* Hong-li Yan,2 Jian-hua Wu1 1Department of Dermatology, Changhai Hospital, Naval Medical University, Shanghai, People’s Republic of China; 2Center for Reproductive Medicine, Changhai Hospital, Naval Medical University, Shanghai, People’s Republic of China; 3Shanghai International Travel Healthcare Center, Shanghai Customs District, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian-hua Wu, Department of Dermatology, Changhai Hospital, Naval Medical University, Shanghai, People’s Republic of China, Email wujh_chyy@163.com Hong-li Yan, Center for Reproductive Medicine, Changhai Hospital, Naval Medical University, Shanghai, People’s Republic of China, Email hongliyan@smmu.edu.cnBackground: It has been shown that the Basal cell carcinoma (BCC) is associated with chronic inflammation of skin conditions, the circulating inflammatory protein levels may be a more intuitive index in response to inflammation, however, the cause-and-effect relationship between circulating inflammatory proteins and BCC is currently unknown.Methods: This study performed a Mendelian randomization (MR) analysis using the plasma inflammatory protein levels from a large genome-wide protein quantitative trait loci study as the exposure data, and the outcome data from a GWAS for BCC. Inverse variance weighed, MR-Egger, maximum likelihood ratio, and weighted median for assessing causality between inflammatory proteins and BCC. MR-Egger regression and Cochran’s Q statistic were applied for sensitivity analysis and MRPRESSO was applied to exclude outliers. Inverse MR analysis was performed on inflammatory proteins found to be causally associated with BCC.Results: Six circulating inflammatory proteins with a causal relationship with BCC were obtained, including CCL4, was of a significant protective effect on BCC development. IL-18 and CCL28, were of suggestive protective effects on BCC development. CX3CL1, IL-17A, and CSF-1 were potential risk factors in the development of BCC. According to the results of reverse MR analysis, there is no significant causal relationship between BCC and the above-mentioned inflammatory proteins.Conclusion: This two-sample MR study revealed a strong association between circulating inflammatory proteins and the development of BCC. Specifically, CCL4, CCL28, IL-18, CX3CL1, IL-17A, and CSF-1 emerged as potential targets for prognostic evaluation and treatment of BCC. However, further experimental studies are needed to elucidate the specific mechanisms.Keywords: Mendelian randomization, basal cell carcinoma, circulating inflammatory proteins, GWAS